Morphometric of Tiger Shrimp (Penaeus monodon) Caught at Night in Samboja Waters Kutai Kartanegara Regency - Harlianti, Nabilla Oktavia; Syahrir R, Muhammad; Abdunnur, Abdunnur (Faculty of Fisheries and Marine Science, Mulawarman University, 2023)
Tiger prawn (Penaeus monodon) is a type of shrimp from the Penaeidea family and is one of the caught in Samboja waters. This research was conducted in November-December 2022 in Samboja Kuala Waters, Kutai Kartanegara by catching shrimp at night using trawl fishing gear. The sample used was 100 tiger prawns (Penaeus monodon) with 42 females and 58 males. This study aims to determine the morphometric characters of tiger shrimp (Penaeus monodon) and to analyze the morphometric measurements. In the analysis using Ancova, the results obtained were 12 morphometric characters of tiger shrimp (Penaeus monodon) with significant values greater than 0.05, namely RST, PK, PRT, PRN, PT, PP, PKB, PTB, PNB, PE and PTK . So based on the initial hypothesis, if the significant number is greater than 0.05 Ho, it is accepted, which means that there is no relationship between the morphometrics of male and female tiger shrimp (Penaeus monodon).